Asynchronous Posting and Reading both Reflect Communities of Inquiry - Kaur Magon, Juss; Shore, Bruce M. (International Journal for Talent Development and Creativity)

(untitled) (International Centre for Innovation in Education/Lost Prizes International, 2022)
This descriptive case study explored the presence of a community of inquiry among 4492 secondary learners enrolled in four asynchronous online discussion forums over a full year. The forums (Ethics and Philosophy, Reading, Astronomy and Space, and General Debates, among others not studied) were external to the students’ schools across England. The data had been archived by the sponsoring organisation. We coded 3,113 transcribed messages posted or read by students using Garrison’s Community-of-Inquiry model and coding tools--addressing social, cognitive, and teaching presence within the interactions, plus 307 online questionnaire responses from a cross-section of participants about reasons for posting or not and overall participation plus representative quotes were also presented. Of the 4,492 enrollees, 1,523 (34%) posted messages, 1,748 (39%) only read or viewed posts, and 1,222 (27%) never logged in. This posting rate was almost quadruple the rate previously reported for online communities. Participation was also wider. The largest numbers of messages reflected community-of-inquiry social presence, especially following-up others’ messages. Cognitive presence particularly reflected sharpening thinking skills and knowledge. Teaching presence included asking stimulating questions and providing encouragement. Students who only viewed others’ messages logged in frequently, reported stimulation and strong benefits in learning skills, and only occasionally reported shyness or intimidation. Active student participation and engagement include more than posting messages; they also include reading or viewing others’ posts. Community of inquiry was highly evident in the asynchronous, secondary, online setting. An asynchronous platform, with effective teaching presence, can support important qualities of a community of inquiry.